Delta-opioid receptor analgesia is independent of microglial activation in a rat model of neuropathic pain. - Joanna Mika (Public Library of Science (PLoS), 2014)
The analgesic effect of delta-opioid receptor (DOR) ligands in neuropathic pain is not diminished in contrast to other opioid receptor ligands, which lose their effectiveness as analgesics. In this study, we examine whether this effect is related to nerve injury-induced microglial activation. We therefore investigated the influence of minocycline-induced inhibition of microglial activation on the analgesic effects of opioid receptor agonists: morphine, DAMGO, U50,488H, DPDPE, Deltorphin II and SNC80 after chronic constriction injury (CCI) to the sciatic nerve in rats. Pre-emptive and repeated administration of minocycline (30 mg/kg, i.p.) over 7 days significantly reduced allodynia and hyperalgesia as measured on day 7 after CCI. The antiallodynic and antihyperalgesic effects of intrathecally (i.t.) administered morphine (10-20 µg), DAMGO (1-2 µg) and U50,488H (25-50 µg) were significantly potentiated in rats after minocycline, but no such changes were observed after DPDPE (10-20 µg), deltorphin II (1.5-15 µg) and SNC80 (10-20 µg) administration. Additionally, nerve injury-induced down-regulation of all types of opioid receptors in the spinal cord and dorsal root ganglia was not influenced by minocycline, which indicates that the effects of opioid ligands are dependent on other changes, presumably neuroimmune interactions. Our study of rat primary microglial cell culture using qRT-PCR, Western blotting and immunocytochemistry confirmed the presence of mu-opioid receptors (MOR) and kappa-opioid receptors (KOR), further we provide the first evidence for the lack of DOR on microglial cells. In summary, DOR analgesia is different from analgesia induced by MOR and KOR receptors because it does not dependent on injury-induced microglial activation. DOR agonists appear to be the best candidates for new drugs to treat neuropathic pain.